2021
DOI: 10.3126/janr.v4i1.33374
|View full text |Cite
|
Sign up to set email alerts
|

Late blight of potato and its management through the application of different fungicides and organic amendments: a review

Abstract: Late the blight  of  potato is  a  devastating  and  one of  the  economic diseases  of potato  and  other plants  belonging  to family Solanaceae. Late blight, caused by Phytophthora infestans, is one of the most threatening pathogenic diseases which not only results in direct crop losses but also cause farmers to embrace huge monetary expenses for disease control and preventive measure. It was first reported during the Irish Potato Famine, leading to massive starvation in Ireland and other parts of Europe du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Generally, increasing rainfall and RH provided conducive conditions for P. infestans proliferation. These results are in agreement with previous reports (Baker et al, 2015;Naerstad et al, 2007;Tiwari et al, 2021) which showed the significance of weather in the progression of late blight epidemics. However, we noted that disease progress 77 days after emergence coincided with low rainfall and declining RH below the 95% (RH) during the last phase of crop growth.…”
Section: Discussionsupporting
confidence: 94%
“…Generally, increasing rainfall and RH provided conducive conditions for P. infestans proliferation. These results are in agreement with previous reports (Baker et al, 2015;Naerstad et al, 2007;Tiwari et al, 2021) which showed the significance of weather in the progression of late blight epidemics. However, we noted that disease progress 77 days after emergence coincided with low rainfall and declining RH below the 95% (RH) during the last phase of crop growth.…”
Section: Discussionsupporting
confidence: 94%
“…These phytopathogenic fungi are very deleterious due to their severe effects and resistance ability for many fungicides. So, the control of these pathogens is a very urgent approach to maintain Temperature plays an important role in its life cycle, where sporangia of P. infestans can germinate by a single germ tube at 13-21°C, and the emergence of late blight is accompanied by a moderate temperature (10-16°C) and high relative humidity [21,22]. The fungal growth is inhibited at 30°C or more, and it can further sporulate when the temperature be relatively moderate with high relative humidity near 100% [19].…”
Section: Phytophthora Diseases In Egyptmentioning
confidence: 99%
“…The second phase of the life cycle starts in the moist soil bearing sporangia. Zoospores profusely germinate and penetrate the tubers through the wounds [21,22].…”
Section: Phytophthora Diseases In Egyptmentioning
confidence: 99%
See 1 more Smart Citation
“…If yield losses by pathogens are reduced, potato has the potential to meaningfully assist in achieving the first United Nations Organization’s ( Quiroz et al, 2018 ) development goal of eliminating poverty and malnutrition in the world ( Chávez-Dulanto et al, 2021 ). Recent decades have witnessed a drastic change in the popularity of potatoes in Asian and African countries, which previously depended on other food crops ( Tiwari et al, 2021 ). Therefore, the ever increasing preference of potato consumption necessitates sustainable approaches to ensure the stability of potato production are a must ( Kroschel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%